KOMUNIKASI KELOMPOK DAN KESEJAHTERAAN SOSIAL: Studi Deskriptif Kualitatif Tentang Komunikasi Kelompok Karang Taruna Mekar Remaja dalam Meningkatkan Kesejahteraan Sosial di Dusun Grasak Kismoyoso Boyolali - Djaya, Tika Ristia (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2013)
The objectives of the research are to study about group communication which are conducted by the members of â€™â€™Mekar Remajaâ€™â€™ youth association and to know about the roles of its members in improving social welfare. This research used descriptive and qualitative method to explain about various phenomena that occur in the field. The location of this research is in Grasak village Kismoyoso Boyolali, the data of this research were gained by doing interview, observation, and documentation. Sampel of this data are four members of â€™â€™Mekar Remajaâ€™â€™ youth association and two people who are not members of this association. The result of analysis which is conducted by the writer are: group communication which are conducted by â€™â€™Mekar Remajaâ€™â€™ youth association is two ways communications that are: face to face communication, and communication through media (hand phone and invitation) and conducting regular meeting every 35 days, this event has been effective. Another activities which are held by â€™â€™Mekar Remajaâ€™â€™ youth association such as: entrepreneurship, community service, â€sinomanâ€, sport activities, â€™â€™halal bi halal, â€™â€™Idul Adhaâ€™â€™, and held many events to celebrate the independence day. Members of â€™â€™Mekar Remajaâ€™â€™ youth association can maintain the group communication which is already effective, and improve the entrepreneur activities and other positive activities in order to increase the social welfare in Grasak village Kismoyoso Boyolali.